Methanolic extract of Urochloa humidicola on in vitro rumen fermentation - Freitas, Rafaela Scalise Xavier de; Nepomuceno, Delci de Deus; Modesto, Elisa Cristina; Pereira, Tatiana Pires; Almeida, João Carlos de Carvalho; Morais, Leonardo Fiusa; Pereira, Luiz Gustavo Ribeiro; Machado, Fernanda Samarini; Campos, Mariana Magalhaes; Tomich, Thierry Ribeiro (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effect of the addition of the methanolic extract of Urochloa humidicola at four different concentrations (0, 75, 150, and 250 g L-1) on the in vitro rumen fermentation of Urochloa brizantha. The following variables were evaluated by the in vitro gas production technique: kinetic parameters; rumen degradation of dry matter; and production and concentration of the methane and carbon dioxide gases and of the acetate, propionate, and butyrate short-chain fatty acids. The addition of the methanolic extract reduces the production of gases generated from the degradation of non-fibrous carbohydrates (fraction A) in 9.55, 6.67, and 13.33%, respectively, at the concentrations of 75, 150, and 250 g L-1, compared with the control group, but it negatively affects the degradation of the dry matter of U. brizantha at the concentrations of 150 and 250 g L-1. The extract shows negative quadratic effect on gas production during 12 and 24 hours of U. brizantha incubation. The extract of U. humidicola reduces methane production and increases short-chain fatty acid production at the concentrations of 75, 150, and 250 g L-1.